1976
DOI: 10.1113/jphysiol.1976.sp011226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isopropylnoradrenaline on tachyphylaxis of gastrin stimulated gastric acid secretion and mucosal blood flow in the anaesthetized cat.

Abstract: SUMMARY1. Gastric acid and mucosal blood flow responses to sustained gastrin stimulation were studied in anaesthetized cats.2. Acid and mucosal blood flow showed identical rates of tachyphylaxis to both large (maximal) and small doses of gastrin.3. Isopropylnoradrenaline infused either intravenously or close arterially to the stomach produced increases in blood flow unrelated to time following the peak response to large doses of gastrin, whereas increases in acid secretion appeared to be a part removal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…This would necessitate a marked endogenous histamine drive since metiamide is equipotent in inhibiting exogenous histamine and pentagastrin stimulated secretion (Black et al 1973;Konturek et al 1974). Reed & Smy (1976) suggested that gastric acid tachyphylaxis to gastrin may be partly explained by a primary tachyphylaxis of gastric mucosal blood flow to gastrin. However, if this mechanism is important SOMATOSTATIN AND H+ TACHPYHYLAXIS in determining tachyphylaxis, then we must assume that it is influenced by Somatostatin and not by metiamide from the evidence given above (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would necessitate a marked endogenous histamine drive since metiamide is equipotent in inhibiting exogenous histamine and pentagastrin stimulated secretion (Black et al 1973;Konturek et al 1974). Reed & Smy (1976) suggested that gastric acid tachyphylaxis to gastrin may be partly explained by a primary tachyphylaxis of gastric mucosal blood flow to gastrin. However, if this mechanism is important SOMATOSTATIN AND H+ TACHPYHYLAXIS in determining tachyphylaxis, then we must assume that it is influenced by Somatostatin and not by metiamide from the evidence given above (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is necessary to explain reversal of acid tachyphylaxis to pentagastrin produced by isopropyl-noradrenaline since this totally reverses the tachyphylaxis (Reed & Smy, 1976). It is possible that its action depends upon a fi-adrenergic effect on the gastrin receptors distinct from its action on blood vessels such that it alters the binding characteristics of gastrin and thus prevents tachyphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…5). Neither adrenoreceptor antagonist altered the fade in response to either dose of pentagastrin (Table 1) In the anaesthetized cat, isoprenaline has been reported to result in a reversal of pentagastrin fade (Reed & Smy, 1976). Isoprenaline (4 ,ug kg-1 h-1) did not effect the maximum secretion to 1 jug pentagastrin kg-' h-1, although the response tended to be reduced in the later part of the experiment (Fig.…”
Section: Gastric Acid Secretion Fade Pentagastrin Fade During a Backgmentioning
confidence: 95%
“…During simultaneous measurement of gastric mucosal blood flow and acid secretion in anaesthetized cats, isoprenaline was able to at least partially reverse fade of pentagastrin-stimulated acid secretion, whilst increasing mucosal blood flow. Thus it was suggested that fade of gastric acid secretion was secondary to a primary fade of mucosal blood flow (Reed & Smy, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In other experimental animals these agents have been found to increase gastric mucosal blood flow (Curwain & Holton, 1972;Reed & Smy, 1976). Of interest also is the finding that incubation of rat stomach fundus and other tissues with catecholamines in vitro increased the production of prostaglandin E (Pace-Asciak, 1972;Collier, McDonald-Gibson & Seed, 1976) which has the property of protecting gastric mucosa against injury (Robert, Nezamis, Lancaster & Hanchar, 1979).…”
Section: Introductionmentioning
confidence: 99%